SOME NEW ASPECTS OF UNDERSTANDING GRIGOL ROBAKIDZE'S "MY EXPLANATION" - Meri Mamagulishvili (The Conference Hub, 2025)
In 1939, Grigol Robakidze's essay dedicated to Adolf Hitler was published. Eight years later, the author returned to the aforementioned work and wrote not a new version or an editorial, but a kind of documented confession - "My Explanation", whichconsists of both descriptive (autobiographical, memoir) and conceptual parts. Here the author deliberately does not touch on the well-established literary appearance of the essay, he has made the subject of necessary interpretation that which is "more than a literary work" in the essay. That is, the meaning of what is said. The essay is also a kind of anamnesis of the style and method of thinking of German society, which, from the point of view of the perception of the text, does not fully coincide with the author's potential desire. "My Confession" is an excellent example of what the author expects from his own intellectual product and what he ultimately receives. In accordance with the reader's feedback, rethinking the work within the framework of new works is not a frequent occurrence in writing. Keywords: Adolf Hitler, Myth, Metaphysics